Basic provisions of the program of increase of efficiency of technique of rowing movements of sportswomen in synchronized swimming - Литвиненко, Юрий (Slobozhanskyi Herald of Science and Sport, 2016)
Lytvynenko, Yu. Purpose: the development and the check of efficiency of the program, which is directed to the improvement of technique of rowing movements in "horizontal" basic positions of the obligatory program of sportswomen of 11–12 years old, who specialize in synchronized swimming. Material & Methods: theoretical analysis and synthesis of data of special literature, pedagogical experiment, anthropometry, methods of registration and analysis of movements, qualimetry and mathematical statistics. Results: the program, which is directed to the improvement of technique of "standard" rowing movement in "horizontal" basic positions of the obligatory program of sportswomen of 11–12 years old, who specialize in synchronized swimming, is proved and approved experimentally. Conclusions: the assessment of experts for the performance of "horizontal" basic positions at sportswomen of the experimental group grew statistically significantly as a result of the made forming experiment (р<0,05). Positive changes were also noted on indicators of the biomechanical structure of technique in the experimental group. The nature of the noted change is connected with the approach of features of motive actions by the second way of "standard" rowing movement.